Outcome and Adverse Drug Reactions of Shorter Versus Longer Regimen of Drug-Resistant Tuberculosis Treatment in a Tertiary Care Respiratory Centre - Nager Devi Vampanan; Shamala Balan; Zamzurina Abu Bakar; Nurul Nabihah Hilmiyah; Khoo Ming Yi; Lim Suat Yee (Asian Journal of Medicine & Health Sciences, 2024)
Drug-resistant tuberculosis (DR-TB) remains a global threat. Evidence on the outcomes and adverse drug reactions (ADRs) of DR-TB management with shorter (STR) or longer (LTR) treatment regimens is limited. This study characterised the outcomes and ADRs of STR and LTR for DR-TB patients at a tertiary care respiratory centre. A retrospective cross-sectional study was conducted among adult DRTB patients attending the Respiratory Clinic of the Institute of Respiratory Medicine, Malaysia from January 2015 to January 2021. Medical records and ADR forms were screened for DR-TB treatment outcome and ADR information. Treatment outcomes were classified as successful or unsuccessful. Descriptive analysis was performed using SPSS version 20. Eighty-four patients aged 18 to 68 years old (41.2±14.2) were included. The DR-TB treatment consists of 42.9% (n = 36) patients in STR and 57.1% (n = 48) patients in LTR. Overall, 52.8% (n = 19) and 54.2% (n = 26) patients were categorised as having successful outcomes in the STR and LTR, respectively. Sixty-two (73.8%) patients experienced at least one ADR resulting in 110 ADR cases. Most ADRs (n = 80, 72.7%) were reported among LTR patients. The suspected drugs were mostly kanamycin (n = 32, 29.1%), cycloserine (n = 22, 20%) and ethambutol (n = 20, 18.2%). The most common ADRs involved the gastrointestinal disorders (n = 40, 36.4%). Majority of serious ADRs (n = 46/55, 83.6%) were observed in the LTR. Treatment success and occurrence of ADRs were higher in the DR-TB patients on LTR. Assessment of key factors that influence treatment decisions should be explored to guide the selection of appropriate treatment regimens.